2023
DOI: 10.37689/acta-ape/2023ao02882
|View full text |Cite
|
Sign up to set email alerts
|

Medidas antropométricas associadas ao tempo de encarceramento de pessoas privadas de liberdade

Abstract: Medidas antropométricas associadas ao tempo de encarceramento de pessoas privadas de liberdadeAnthropometric measures associated with incarceration length of persons deprived of their liberty Medidas antropométricas relacionadas con el tiempo de encarcelamiento

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…In accordance with Table 1, from June to November 2019, in another prison facility in the state of Paraná, Baccon et al (2023) carried out a study that reported similar findings regarding the age of inmates, the average age was 30.9 with a standard deviation of 10.1, encompassing subjects aged 19 to 64, which underscores a characteristically young prison population when analyzing the age group. A comparative analysis with the study by Costa et al (2023), which explored the sociodemographic profile of inmates in a penitentiary in Foz do Iguaçu-PR in 2021, revealed striking similarities between the two categories (married and single), the authors found 43.3% single subjects compared to 42.3% married, with 58.6% reporting having children.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In accordance with Table 1, from June to November 2019, in another prison facility in the state of Paraná, Baccon et al (2023) carried out a study that reported similar findings regarding the age of inmates, the average age was 30.9 with a standard deviation of 10.1, encompassing subjects aged 19 to 64, which underscores a characteristically young prison population when analyzing the age group. A comparative analysis with the study by Costa et al (2023), which explored the sociodemographic profile of inmates in a penitentiary in Foz do Iguaçu-PR in 2021, revealed striking similarities between the two categories (married and single), the authors found 43.3% single subjects compared to 42.3% married, with 58.6% reporting having children.…”
Section: Discussionsupporting
confidence: 71%
“…Notably, 10.27% of our sample is reported as divorced, suggesting the potential existence of prior marital ties, alongside the presence of children. Compared to the findings of this study Baccon et al (2023), which explored anthropometric measurements and sociodemographic characteristics of incarcerated individuals in northern Paraná, notable parallels were observed. In their study encompassing a total of 220 subjects, 115 (52.3%) had educational attainment of less than eight years, signifying that they did not complete primary education.…”
Section: Discussioncontrasting
confidence: 54%